2014
DOI: 10.1021/ic5015384
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mechanosynthesized Azine-Decorated Zinc(II) Metal–Organic Frameworks for Highly Efficient Removal and Extraction of Some Heavy-Metal Ions from Aqueous Samples: A Comparative Study

Abstract: The three zinc(II) metal-organic frameworks [Zn2(oba)2(4-bpdb)]·(DMF)x (TMU-4), [Zn(oba)(4-bpdh)0.5]n·(DMF)y (TMU-5), and [Zn(oba)(4-bpmb)0.5]n·(DMF)z (TMU-6) [DMF = dimethylformamide, H2oba = 4,4'-oxybisbenzoic acid, 4-bpdb = 1,4-bis(4-pyridyl)-2,3-diaza-1,3-butadiene, 4-bpdh = 2,5-bis(4-pyridyl)-3,4-diaza-2,4-hexadiene, and 4-bpmb = N(1),N(4)-bis((pyridin-4-yl)methylene)benzene-1,4-diamine], which contain azine-functionalized pores, have been successfully synthesized by mechanosynthesis as a convenient, rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(105 citation statements)
references
References 58 publications
2
99
0
4
Order By: Relevance
“…According to the results given in Table 5, the adsorption ability of DPA-LDH toward Pb 2+ and Cu 2+ is higher than that of the other ions. As shown in Table 5 Table 6 shows that the obtained K d values for DPA-LDH are higher than those that were reported for previous sorbents such as metal-organic frameworks [6], dodecyl sulfate based intercalated-LDHs [28], carbonate based LDHs [29], sulfide based intercalated-LDHs and materials [10,40,41], polymers [42,43], magnetic nanoparticles [44,45], ion imprinted polymers [46], layered hydrogen metal sulfides [47], and zeolites [48]. The comparison of the q m values of DPA-LDH with the same values of other sorbents presented in the literature (Table 6) for metal ions removal is indicative of the higher efficiency of DPA-LDH for the removal of heavy-metal ions.…”
Section: Evaluating the Affinity Of Dpa-ldh Toward The Metal Ionsmentioning
confidence: 59%
See 1 more Smart Citation
“…According to the results given in Table 5, the adsorption ability of DPA-LDH toward Pb 2+ and Cu 2+ is higher than that of the other ions. As shown in Table 5 Table 6 shows that the obtained K d values for DPA-LDH are higher than those that were reported for previous sorbents such as metal-organic frameworks [6], dodecyl sulfate based intercalated-LDHs [28], carbonate based LDHs [29], sulfide based intercalated-LDHs and materials [10,40,41], polymers [42,43], magnetic nanoparticles [44,45], ion imprinted polymers [46], layered hydrogen metal sulfides [47], and zeolites [48]. The comparison of the q m values of DPA-LDH with the same values of other sorbents presented in the literature (Table 6) for metal ions removal is indicative of the higher efficiency of DPA-LDH for the removal of heavy-metal ions.…”
Section: Evaluating the Affinity Of Dpa-ldh Toward The Metal Ionsmentioning
confidence: 59%
“…At trace levels, some of the heavy metals such as copper and zinc are essential micronutrients for plants, living organisms, and the human body, whereas, in large amounts, they cause Wilson̕ s, Menkes, and Prion diseases [5]. On the other hand, lead, cadmium are well recognized to be highly toxic and hazardous to human health even at low concentrations [6,7]. Lead can cause central nervous system damage.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal methods are simple and effective techniques which include thermal decomposition and calcination [37][38][39][40][41][42][43]. Thermal decomposition, or thermolysis, is a chemical decomposition caused by heat [44][45][46][47][48][49][50][51].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…The group of Morsali have also investigated the Zn(II)-based MOFs, [Zn 2 (oba) 2 (4-bpdb)]·(DMF) x (TMU-4), [Zn (oba) (4-bpdh) 0.5 ] n ·(DMF) y (TMU-5), [Zn (oba) (4-bpmp) 0.5 ] n ·(DMF) z (TMU-6). They found that the MOFs could be used as solid base catalysts in the Knoevenagel condensation because of the basicity of azine functionalized pores [87] and among the three MOFs, TMU-6 had a lower adsorption efficiency for metal ions than the other two MOFs, which was attributed to the greater basicity of the azine groups on the TMU-4 and TMU-5 pore walls as compared to the imine groups on the N-donor ligands on the TMU-6 pore walls [88].…”
Section: Affinity For Organic Moleculesmentioning
confidence: 99%